Besarnya Tegangan Tarik Yang Diizinkan Pada Rantai Untuk Memutar Tippler Lori Yang Berisi Tandan Buah Matang (TBM) di PT Z - Juliastio Saputra Tarigan; Herry Darmadi; Dian Kurnia (JURNAL VOKASI TEKNIK, 2023)
Chain is a series of links or rings that are connected or attached to one another so that they form an elongated shape. Chains are used to move loads or as a substitute for additional power. One of the chains that is often used is made of the hardest metal, namely steel. One of them is a chain roller attached to the Tippler, where this chain functions to pour ripe fruit bunches from the lorry. The purpose of this research is to determine the performance of Tippler to rotate Tippler Lori containing Ripe Fruit Bunches. Based on the calculations that the author has carried out, the amount of load that occurs on the chain is 5610 Kgf. And the allowable Tensile Stress in the chain is 1225 Mpa.